Infectious : pathogens and how we fight them - Tregoning, John (Oneworld, 2021)
Nature wants you dead. Not just you, but your children and everyone you have ever met and everyone they have ever met; in fact, everyone. It wants you to cough and sneeze and poop yourself into an early grave. It wants your blood vessels to burst and pustules to explode all over your body. And - until recently - it was really good at doing this. Covid-19 may be only the first of many modern pandemics. The subject of infection and how to fight it grows more urgent every day. How do pathogens cause disease? And what tools can we give our bodies to do battle?